Analysis of the zakat village model for economic sector utilization: ANP approach - Fitri Annisa Fitri; Efi Syarifuddin; Sarehan Sulong (Jurnal Ekonomi dan Keuangan Islam, 2024)
Purpose – This study evaluates the economic sectors of the Zakat Village Program by identifying the objectives, criteria, and risks. Methodology – This study uses a qualitative Analytic Network Process (ANP) approach to determine the order of priorities and decision-making. Data were collected through interviews and questionnaires with expert respondents in the field of zakat utilization and empowerment. Finding – This research shows that the village zakat program plays an important role in overcoming economic problems. However, experts believe that the aspect of determining activities is still considered low. Implication – The findings of this study contribute to the enhancement of zakat village program planning, so that the objective components of the zakat village program can be expressed more clearly and in detail in the future. Originality – This original study collected the views of experts in evaluating village zakat programs by confirming them through the geometric mean as a priority value for each objective, criteria, main criteria, and risk.